Linkage and sequence analysis in families - Amos, Christopher (Henry Stewart Talks, 2017)
Meiosis and linkage, Family structure and phasing of gametes, The Elston-Stewart and Lander Green likelihood formulations, Model-free tests, Sequencing analysis, Example of linkage and sequencing in a family study